KUR'AN IŞIGINDA iNSANIN BiREYSEL SORUMLULUGU (Günah ve Sevap) - Yeşilyurt, Temel (Fırat University, 2005)
This essay has discussed the fact of sin-reward (gunah-sevap) in front of the personal responsibility according to the Qur'an. But it is based especially on the Qur'an and there aren't any detailed theological discussions. The Qur'an defıne the human as a exist who is a free on the personal !eve! and capable his activities. This freedom forrns the reasons for the responsibility of their activities. There i sn 't hereditary sin in the Qur'an. Every human, says the Qur'an, will see the suitable punishment for only their activities.
Keywords: Religious Studies; Din Araştırmaları